A documentation of rare species, and Iowa Ornithologists Union fall field notes, 1978 - Stone, Tom, Jr.et al (1978)
Rare bird sighting documentation for a Black Legged Kittiwake and field report titled "Iowa Ornithologists Union fall report", submitted by Tom Stone Jr., December 3, 1978. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1978. Epson - sheet feed/flatbed